370 Title correlates of presenteeism: a study of nurses working in geriatric settings in malta. (24th April 2018) - Fiorini, L; Griffiths, A; Houdmont, J
Abstract : Introduction: Presenteeism is usually defined as attending for work while ill. It is linked with lost productivity and increased sickness absence, and can be costly to organisations. Studies suggest a high prevalence of presenteeism in the healthcare sector. Additionally European statistics suggest that presenteeism is particularly frequent in Malta (EU). A study was therefore conducted to investigate the correlates of presenteeism in a sample of nurses working within a geriatric ward setting in Malta. Methods: A cross-sectional survey (n = 270) investigated the suggested predictors of presenteeism that had emerged in an earlier qualitative study. Hierarchical binary logistic regression was used to identify the correlates of presenteeism. Data was analysed using SPSS. Result: Individuals who had engaged in presenteeism two or more times in the previous 12 months were more likely to have: engaged in sickness absenteeism frequently (OR 2.36, 95% CI: 1.02 to 5.94); felt emotional during their last presenteeism episode (OR 1.21, 95% CI: 1.07 to 1.37); felt that their last sickness absenteeism episode was good for their health (OR 1.72, 95% CI: 1.14 to 2.61); and felt presenteeism was necessary following recent sick leave (OR 1.45, 95% CI: 1.08 to 1.94). They were also less likely to have: reported a fracture (OR 0.06, 95% CI: 0.01 to 0.63) or gastric illness (OR 0.35, 95% CI: 0.15 to 0.82) during their last absenteeism episode; understood the illness that led to their last presenteeism episode (OR 0.80, 95% CI: 0.67 to 0.95); and to feel that they had managerial and peer support (OR 0.45, 95% CI: 0.26 to 0.91). Discussion: The study highlights that presenteeism is linked to overall health, however perceptions of individual illnesses can also influence the frequency of this behaviour. The study also supports previous findings that work attitudes and organisational factors also play a role. Interventions that benefit nurses' health and provide support at work may reduce the frequency of presenteeism.